Telemedicine Improves the Short-Term Medical Care of Acute ST-Segment Elevation Myocardial Infarction After Primary Percutaneous Coronary Intervention - Kamel, Heba; Hafez, Mohamed Saber; Bastawy, Islam (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Telemedicine appears to be a promising tool for healthcare professionals to deliver remote care to patients with cardiovascular diseases especially during the COVID-19 pandemic. We aimed in this study to evaluate the value of telemedicine added to the short-term medical care of acute ST-segment elevation myocardial infarction (STEMI) after the primary percutaneous coronary intervention (PCI). Methods: Two hundred acute STEMI patients after primary PCI were randomly divided into 2 groups. One hundred patients in group A (study group) received a monthly videoconferencing teleconsultation using a smartphone application for 3 months starting 1 week after discharge and at least a single face-to-face (F2F) clinic visit. We reviewed in each virtual visit patients' symptoms, adherence to healthy lifestyle measures, medications, smoking cessation, and cardiac rehabilitation. While group B (control group) included 100 patients who received at least a single F2F clinic visit in the first 3 months after discharge. Both groups were interviewed after 4 months from discharge for major adverse cardiac events (MACE), adherence to medications, smoking cessation, and cardiac rehabilitation. A survey was done to measure patients satisfaction with telemedicine. Results: There was no significant difference between both groups in MACE, patients' adherence to aspirin, P2Y12 inhibitor, and beta-blockers. However, Group A patients had better adherence to statins, angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, smoking cessation, and cardiac rehabilitation. Sixty-one percent of patients stated that these videoconferencing teleconsultations were as good as the clinic visits, while 87% of patients were satisfied with telemedicine. Conclusions: Telemedicine may provide additional benefit to the short-term regular care after primary PCI to STEMI patients through videoconferencing teleconsultations by increasing their adherence to medications and healthy lifestyle measures without a significant difference in the short-term MACE. These virtual visits gained a high level of patients satisfaction.